Pour une éthique de la dette écologique - Julien Delord; Léa Sébastien (VertigO, 2010)
We propose an ethical background to the internationally emergent concept of “ecological debt”. We assume that the new generation of environmental philosophers will have to think the catastrophe, not on a future perfect mode like Jean-Pierre Dupuy or Hans Jonas’ theories, but on a past conditional mode. We refuse Dupuy’s “memory of the future” in order to reexplore the ecological memories of past and current catastrophes as a way to discuss the norms for the future. The notion of ecological debt invites us precisely to discuss a new environmental ethics based on past ecological faults.The imperative of an environmental responsibility from present generations towards future generations goes necessarily along with the acknowledgement of a massive ecological debt left by past generations to the present generation. Is it possible, not to say mandatory, to cancel and forgive this debt ? But, is forgiving the catastrophe not leading us to renounce to any consistent responsibility between generations and to miss the opportunity to reach a global and efficient environmental ethics ? After an historical reminder of the genesis of the notion of ecological debt, which can be defined as the totality of past environmental damages due to human activity and not compensated until the present, we put forward a model of past counterfactual responsibility both on a theoretical and a practical level. Eventually, two applied examples are discussed : one about a private and territorialized industrial debt due to decades of pollutions, and another one about a public and global debt, the climate debt.